2003
DOI: 10.1007/s005950300039
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Roux-en-Y Reconstruction After Distal Gastrectomy Based on an Assessment of Biliary Kinetics

Abstract: In this series, RY was found to be a superior reconstruction method after distal gastrectomy since it was rarely accompanied by the reflux of duodenal juice into the remnant stomach or gastric reflux into the lower esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
48
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 17 publications
3
48
2
Order By: Relevance
“…We previously evaluated short-term outcomes after LDG and reported several advantages of R-Y over B-I, consistent with the results of the present study [15]. Previous studies of short-term outcomes have shown that R-Y reconstruction, compared with B-I, is associated with lower incidences of gastroesophageal reflux, bile reflux, and remnant gastritis on endoscopic examination [12,[20][21][22]. Gastroesophageal reflux, as assessed by dynamic scintiscan, is also less frequent after R-Y than after B-I [23].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We previously evaluated short-term outcomes after LDG and reported several advantages of R-Y over B-I, consistent with the results of the present study [15]. Previous studies of short-term outcomes have shown that R-Y reconstruction, compared with B-I, is associated with lower incidences of gastroesophageal reflux, bile reflux, and remnant gastritis on endoscopic examination [12,[20][21][22]. Gastroesophageal reflux, as assessed by dynamic scintiscan, is also less frequent after R-Y than after B-I [23].…”
Section: Discussionsupporting
confidence: 88%
“…Less gastroesophageal and duodenogastric reflux might underlie the lower incidence of symptoms after R-Y. In other studies [12,21], the proportions of patients with clinical symptoms caused by these types of reflux ranged from 0 to 17 % after R-Y, as compared with 12-63 % after B-I 3-6 months after operation. The incidence of heartburn was lower after R-Y (10 %) than after B-I (37 %) 1 year postoperatively in our previous study [15].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…One incident of Barrett's esophagus in a patient in the B-II with Braun anastomosis group was observed 12 months postoperatively. Shinoto et al [13] also reported that bile reflux in the remnant stomach was significantly less in the R-Y group than in the B-I and B-II groups based on biliary scintigraphy. In our study, the extent of bile reflux in the B-I group was also less but not significantly different from that in the B-II group at 12 months.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, B-I reconstruction has the physiological advantage of permitting the passage of food through the duodenum [16]. However, compared to B-I reconstruction, R-Y reconstruction also has certain advantages, such as a reduction in the incidence of anastomotic leakage and prevention of remnant gastritis and bile reflux into the remnant stomach [7,8,[17][18][19][20][21]. Hence, R-Y reconstruction after LADG has been the firstchoice reconstruction technique at our institution since March 2003.…”
Section: Discussionmentioning
confidence: 99%